Polymer mean spherical approximation for the fluid of flexible hard-sphere Yukawa star molecules - Kalyuzhnyi, Yu.V.; Holovko, M.F. (Condensed Matter Physics, 2002)
An extension of the product-reactant Ornstein-Zernike approach (PROZA) for the fluid of flexible star molecules is proposed and the corresponding version of the mean spherical approximation (MSA), the so-called polymer MSA (PMSA), is formulated. Using Baxter-Wertheim factorization technique, an analytical solution of the PMSA for the fluid of star molecules with Yukawa hard-sphere interaction between the molecular segments is derived and closed form analytical expressions for the Helmholtz free energy, chemical potential and equation of state are presented. The structure properties of several different versions of the star fluid model are studied. Запропоновано узагальнення підходу Орнштейна-Церніке продуктреагент для рідини гнучких зіркових молекул та сформульовано від- повідний варіант середньосферичного наближення (ССН), так зване полімерне ССН (ПССН). На основі методу факторизації Бакстера-Вертхайма отримано аналітичний роз’язок ПССН для рідини зіркових молекул з твердосферною юкавівською взаємодією між сегментами молекул та представлені явні аналітичні вирази для вільної енергії, хімічного потенціалу та рівняння стану. Проведено дослідження структурних властивостей кількох різних варіантів моделі рідини зіркових молекул.